Preparation method of lithium manganese iron phosphate high-energy-density dry-method electrode and binder

The high-energy density electrode of lithium manganese iron phosphate was prepared by dry method, and the materials were dispersed more evenly by using ultrasonic treatment and ball milling technology, which solved the problems of low energy density of existing lithium-ion batteries and time-consuming and labor-consuming electrode preparation, and achieved higher energy density and better mechanical properties.

CN119725406APending Publication Date: 2025-03-28XIAMEN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411908244.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The energy density of existing lithium-ion batteries is low, and traditional wet electrode preparation methods are time-consuming and labor-intensive. The binders used, such as polyvinylidene fluoride (PVDF), cannot transmit electrons and lithium ions, and the use of the toxic solvent N-MP has safety and environmental protection problems.

Method used

The high-energy density electrode of lithium manganese iron phosphate was prepared by dry method. By mixing lithium manganese iron phosphate, conductive carbon black, carbon nanotubes and polymer binder in a specific mass ratio, the material was dispersed more evenly by using ultrasonic treatment and ball milling technology, and finally the electrode was obtained by roll pressing.

Benefits of technology

It improves the energy density of lithium-ion batteries, reduces the use of toxic solvents, enhances the electronic conductivity of the material, and improves the mechanical properties and cycling stability of the electrodes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725406A_ABST
    Figure CN119725406A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a lithium manganese iron phosphate high-energy-density dry-method electrode and a binder. The preparation method comprises the following steps: weighing lithium manganese iron phosphate, conductive carbon black, a carbon nanotube and the binder according to a first mass ratio; putting the weighed carbon nanotubes into a container, and adding absolute ethyl alcohol for ultrasonic treatment to obtain a first solution; pouring the weighed lithium manganese iron phosphate and conductive carbon black into the first solution together, performing ultrasonic treatment to obtain a second solution, and drying the second solution to obtain powder; and mixing the powder with a weighed binder, carrying out ball milling to obtain a flocculent material, and rolling the flocculent material to obtain the electrode. According to the electrode disclosed by the invention, the use of a toxic solvent N-methyl pyrrolidone is reduced, and the energy density is improved; the carbon nanotubes are more uniformly dispersed in the material by using high-frequency ultrasound, so that the electronic conductivity of the material is increased; functional groups on the high-molecular binder have a promoting effect on lithium ion diffusion, and rapid conduction of lithium ions is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a preparation method and a binder for a lithium manganese iron phosphate high energy density dry-process electrode. Background Art

[0002] Lithium-ion batteries (LIBs) have attracted extensive attention from researchers since their commercialization. After more than 30 years of development, the energy density and power density of lithium batteries have been continuously improved under the unremitting efforts of researchers. In order to extend the driving range of electric vehicles, simply improving the energy density of lithium batteries is one of the feasible methods. However, the use of new materials to develop lithium-rich manganese-based cathodes or lithium metal anodes has not yet become a reality. Therefore, the battery structure engineering method that significantly improves the energy density of lithium-ion batteries by increasing the proportion of active materials has attracted the interest of researchers. More specifically, simply increasing the thickness of the electrode is the most effective way to increase the energy density of lithium ions. The wet electrode preparation method is to coat a slurry consisting of active materials, conductive carbon black, binder, and solvent on the current collector, which is time-consuming and labor-intensive. The widely used polyvinylidene fluoride (PVDF) binder cannot transfer electrons and lithium ions, which inevitably reduces the electronic and ionic conductivity of the electrode, resulting in increased resistance and decreased performance. In addition, the solvent of n-methylpyrrolidone (NMP) is toxic and expensive, and it is more energy-consuming to remove it from the electrode due to its high boiling point and low melting point. In addition, the thickness of the electrode prepared by the traditional method is generally less than 100 μm, and the mass loading is also small (cathode 20 mg / cm 2 , anode 10mg / cm 2 ). This is mainly limited by its poor mechanical properties (fragile, brittle, and poor adhesion to the current collector). In traditional electrode preparation, if the slurry coating exceeds a certain thickness, the electrode will break and delaminate during the drying process. Therefore, it is of great significance to develop new technologies for thick electrode preparation with the goal of improving the energy density of lithium-ion batteries. Summary of the invention

[0003] The purpose of the present invention is to overcome the above-mentioned shortcomings of the prior art. On the one hand, the present invention provides a method for preparing a lithium manganese iron phosphate high energy density dry electrode, comprising:

[0004] Weighing lithium manganese iron phosphate, conductive carbon black, carbon nanotubes and a binder according to a first mass ratio;

[0005] Putting weighed carbon nanotubes in a container, adding anhydrous ethanol and performing ultrasonic treatment to obtain a first solution; pouring weighed lithium iron manganese phosphate and conductive carbon black into the first solution, performing ultrasonic treatment again to obtain a second solution, and drying the second solution to obtain a powder;

[0006] The powder is mixed with a weighed binder and ball-milled to obtain a flocculent material, and the flocculent material is roll-pressed to obtain an electrode.

[0007] In one embodiment, the first mass ratio is 85:5:5:5.

[0008] In one embodiment, the mass ratio of anhydrous ethanol to carbon nanotubes is 500:1-750:1.

[0009] In one embodiment, the ultrasonic treatment is as follows: the ultrasonic power is set to 300 W, ultrasonication is performed for 2 seconds and then stopped for 1 second during the ultrasonication process, and the total ultrasonication time is 30 minutes.

[0010] In one embodiment, the second solution is dried in an oil bath to obtain a powder, wherein the temperature of the oil bath drying is 60° C. and the drying time is 15 hours.

[0011] In one embodiment, the binder includes at least one of polytetrafluoroethylene (PTFE), carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR).

[0012] In one embodiment, the binder is PTFE; or the binder is a mixture of PTFE and CMC, with a mass ratio of PTFE to CMC of 3:2; or the binder is a mixture of PTFE, CMC and SBR, with a mass ratio of PTFE, CMC and SBR of 2.5-3.5:0.7-1.3:1.

[0013] In one embodiment, the powder and the weighed binder are weighed according to a second mass ratio, and after weighing, they are put into a ball mill for ball milling, wherein the rotation speed is 300 rpm and the ball milling time is 8 hours.

[0014] In one embodiment, the flocculent material is placed on a roller press and rolled for multiple times to reduce the thickness. When the thickness reaches 165-175 μm, the rolling is stopped to obtain an electrode.

[0015] On the other hand, the present invention also provides a binder for lithium manganese iron phosphate high energy density dry electrode, the binder is a mixture of PTFE, CMC and SBR, and the mass ratio of PTFE, CMC and SBR is 2.5-3.5:0.7-1.3:1.

[0016] The advantages and beneficial effects of the present invention over the prior art are as follows:

[0017] 1. The electrode prepared by the present invention reduces the use of the toxic solvent N-methylpyrrolidone (NMP) and improves the energy density.

[0018] 2. The present invention utilizes high-frequency ultrasound to disperse carbon nanotubes more evenly in the material, thereby increasing the electronic conductivity of the material.

[0019] 3. The present invention utilizes the functional groups on the polymer binder to promote the diffusion of lithium ions and promote the rapid conduction of lithium ions. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0021] Figure 1 The scanning electron microscope images of the electrodes obtained in Example 1, Example 2 and Example 3 of the present invention;

[0022] Figure 2 The magnification and 1C long cycle images of the electrodes obtained in Example 1, Example 2, and Example 3 of the present invention;

[0023] Figure 3 These are EIS images of the electrodes obtained in Example 1, Example 2, and Example 3 of the present invention. DETAILED DESCRIPTION

[0024] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0025] In one aspect, the present invention provides a method for preparing a lithium manganese iron phosphate high energy density dry electrode, comprising:

[0026] Step S10, weighing lithium manganese iron phosphate, conductive carbon black, carbon nanotubes and a binder according to a first mass ratio;

[0027] In this step, the reasons for choosing lithium iron manganese phosphate are: 1. High energy density: Compared with traditional lithium iron phosphate (LFP) materials, lithium iron manganese phosphate has a higher energy density and can provide a larger battery capacity. 2. High safety: Compared with nickel cobalt manganese (NCM) and nickel cobalt aluminum (NCA) materials, lithium iron manganese phosphate has better thermal stability and is not prone to thermal runaway, which improves the safety of the battery. 3. Longer cycle life: It has an excellent cycle life and can maintain a good capacity after multiple charge and discharge cycles. 4. Low cost: Manganese and iron resources are abundant, the cost is relatively low, and it is suitable for large-scale production. 5. Environmentally friendly: It does not contain harmful heavy metals and has little impact on the environment.

[0028] Step S20, placing weighed carbon nanotubes in a container, adding anhydrous ethanol for ultrasonic treatment to obtain a first solution; pouring weighed lithium iron manganese phosphate and conductive carbon black into the first solution, and then ultrasonic treatment to obtain a second solution, and drying the second solution to obtain a powder;

[0029] The reason for segmented mixing: carbon nanotubes are very prone to aggregation. This is because the diameter-surface area and aspect ratio of carbon nanotubes are both very large, which makes the van der Waals force between carbon nanotubes relatively large, causing them to attract each other and aggregate together. We use ultrasound to prevent the nanotubes from being affected by external forces in anhydrous ethanol so that they can be better dispersed. Then, we add the material and conductive carbon black Super P for half an hour of ultrasonic dispersion, so that the material and Super P can be more evenly dispersed in the carbon nanotubes, forming a better all-round conductive network.

[0030] Step S30: Mix the powder with a weighed binder and perform ball milling to obtain a flocculent material, and roll-press the flocculent material to obtain an electrode.

[0031] This step of mixing is based on the conductive network that has already been formed, and then a binder is added to make the materials bond more firmly and make the rolled dry electrode more flexible and tougher.

[0032] Furthermore, the first mass ratio is 85:5:5:5. The ratio of 85:5:5:5 is used to increase the mass of active materials as much as possible to increase the energy density of the battery, but because the particles are too large and the hardness is too high, excessive mass of active materials will cause cracking and sticking to the roller. These problems are particularly evident in the solvent-free electrode rolling process, which makes it impossible to effectively thin the pole piece. Due to the cracking of the pole piece, the material significantly increases the risk of structural failure during battery assembly and cycling. These cracks not only lead to a decrease in coulombic efficiency, but also cause a sharp decay in capacity. Therefore, the ball milling method is used to further reduce the particle size of the particles. After a large number of experiments, the optimal ratio of 85:5:5:5 is obtained. At this ratio, carbon nanotubes and PTFE can build a stable three-dimensional conductive network, making the dry electrode not easy to crack and having the best performance.

[0033] Furthermore, the mass ratio of anhydrous ethanol to carbon nanotubes is 500:1-750:1.

[0034] Furthermore, the ultrasonic treatment is as follows: the ultrasonic power is set to 300 W, the ultrasonic treatment is performed for 2 seconds and then for 1 second, and the total ultrasonic treatment is performed for 30 minutes. Too high ultrasonic power or too long duration will cause certain damage to the carbon nanotubes, such as breakage and fracture.

[0035] Furthermore, the second solution was dried in an oil bath to obtain powder, wherein the temperature during the oil bath drying was 60° C. and the drying time was 15 h.

[0036] Furthermore, the binder includes at least one of polytetrafluoroethylene (PTFE), carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR).

[0037] Furthermore, the binder is PTFE; or the binder is a mixture of PTFE and CMC, with the mass ratio of PTFE to CMC being 3:2; or the binder is a mixture of PTFE, CMC and SBR, with the mass ratio of PTFE, CMC and SBR being 2.5-3.5:0.7-1.3:1.

[0038] Further, the powder and the weighed binder are weighed according to the second mass ratio, and after weighing, they are put into a ball mill for ball milling, wherein the speed is 300 rpm and the ball milling time is 8 hours. If the time is too short, it is not conducive to reducing the particles of lithium manganese iron phosphate. If the speed is too high, the material will be pressed under the ball milling beads during the ball milling process and cannot be evenly mixed.

[0039] Furthermore, the flocculent material is placed on a roller press and rolled for multiple times to reduce the thickness. When the thickness reaches 165-175 μm, the rolling is stopped to obtain an electrode.

[0040] On the other hand, the present invention also provides a binder for lithium manganese iron phosphate high energy density dry electrode, the binder is a mixture of PTFE, CMC and SBR, and the mass ratio of PTFE, CMC and SBR is 2.5-3.5:0.7-1.3:1.

[0041] The present invention has been tested for many times, and some test results are now cited as references to further describe the invention in detail, and the following is a detailed description in conjunction with specific embodiments.

[0042] Example 1

[0043] A method for preparing a lithium manganese iron phosphate high energy density dry electrode, comprising:

[0044] Weigh 4.25 g of lithium manganese iron phosphate, 0.25 g of Super P, 0.25 g of carbon nanotubes and 0.25 g of a binder, wherein the binder is PTFE;

[0045] The weighed carbon nanotubes were placed in a beaker, and 200 ml of anhydrous ethanol was added for high-frequency ultrasonic treatment, wherein the ultrasonic power was set to 300 W, and the ultrasonic process was ultrasonicated for 2 seconds and stopped for 1 second, and the total ultrasonication was 30 minutes to obtain a first solution; the weighed lithium manganese iron phosphate and Super P were poured into the first solution together, and then ultrasonic treatment was performed, wherein the ultrasonic power was set to 300 W, and the ultrasonic process was ultrasonicated for 2 seconds and stopped for 1 second, and the total ultrasonication was 30 minutes to obtain a second solution, and the second solution was dried in an oil bath to obtain a powder, wherein the temperature during oil bath drying was 60° C. and the drying time was 15 hours;

[0046] The powder and binder obtained above are put into a ball mill for ball milling, wherein the rotation speed is 300 rpm and the ball milling time is 8 hours. After the ball milling, a flocculent material is obtained. The flocculent material is put on a roller press and rolled several times to reduce the thickness. When the thickness is 170 μm, the rolling is stopped to obtain an electrode.

[0047] Example 2

[0048] A method for preparing a lithium manganese iron phosphate high energy density dry electrode, comprising:

[0049] Weigh 4.25 g of lithium manganese iron phosphate, 0.25 g of Super P, 0.25 g of carbon nanotubes and 0.25 g of a binder, wherein the binder is a mixture of PTFE and CMC, and the mass ratio of PTFE to CMC is 3:2;

[0050] The weighed carbon nanotubes were placed in a beaker, and 200 ml of anhydrous ethanol was added for high-frequency ultrasonic treatment, wherein the ultrasonic power was set to 300 W, and the ultrasonic process was ultrasonicated for 2 seconds and stopped for 1 second, and the total ultrasonication was 30 minutes to obtain a first solution; the weighed lithium manganese iron phosphate and Super P were poured into the first solution together, and then ultrasonic treatment was performed, wherein the ultrasonic power was set to 300 W, and the ultrasonic process was ultrasonicated for 2 seconds and stopped for 1 second, and the total ultrasonication was 30 minutes to obtain a second solution, and the second solution was dried in an oil bath to obtain a powder, wherein the temperature during oil bath drying was 60° C. and the drying time was 15 hours;

[0051] The powder and binder obtained above are put into a ball mill for ball milling, wherein the rotation speed is 300 rpm and the ball milling time is 8 hours. After the ball milling, a flocculent material is obtained. The flocculent material is put on a roller press and rolled several times to reduce the thickness. When the thickness is 170 μm, the rolling is stopped to obtain an electrode.

[0052] Example 3

[0053] A method for preparing a lithium manganese iron phosphate high energy density dry electrode, comprising:

[0054] Weigh 4.25 g of lithium manganese iron phosphate, 0.25 g of Super P, 0.25 g of carbon nanotubes and 0.25 g of a binder, wherein the binder is a mixture of PTFE, CMC and SBR, and the mass ratio of PTFE, CMC and SBR is 3:1:1;

[0055] The weighed carbon nanotubes were placed in a beaker, and 200 ml of anhydrous ethanol was added for high-frequency ultrasonic treatment, wherein the ultrasonic power was set to 300 W, and the ultrasonic process was ultrasonicated for 2 seconds and stopped for 1 second, and the total ultrasonication was 30 minutes to obtain a first solution; the weighed lithium manganese iron phosphate and Super P were poured into the first solution together, and then ultrasonic treatment was performed, wherein the ultrasonic power was set to 300 W, and the ultrasonic process was ultrasonicated for 2 seconds and stopped for 1 second, and the total ultrasonication was 30 minutes to obtain a second solution, and the second solution was dried in an oil bath to obtain a powder, wherein the temperature during oil bath drying was 60° C. and the drying time was 15 hours;

[0056] The powder and binder obtained above are put into a ball mill for ball milling, wherein the rotation speed is 300 rpm and the ball milling time is 8 hours. After the ball milling, a flocculent material is obtained. The flocculent material is put on a roller press and rolled several times to reduce the thickness. When the thickness is 170 μm, the rolling is stopped to obtain an electrode.

[0057] The scanning electron microscope images of the electrodes obtained in Example 1, Example 2 and Example 3 are as follows: Figure 1 As shown in the figure, the SEM shows that the thickness of the three materials is roughly the same, about 170 μm, and the area loading is about 24 mg / cm 2 , compared with the commercial wet coating surface loading (22mg / cm 2 ) are roughly the same.

[0058] The electrodes obtained in Example 1, Example 2, and Example 3 were assembled into half-cells to test their electrochemical performance. Figure 2 The magnification and 1C long cycle images of the electrodes obtained in Example 1, Example 2 and Example 3 are shown in FIG. Figure 2 It can be seen that the rate performance of the electrode with only one binder (PTFE) dropped sharply at 3C, while the other two electrodes still maintained relatively stable performance at 3C. When the current was further increased to 5C, the electrode with three binders (PTFE CMC SBR) showed the best performance. The half-cells of the three electrodes were tested for a long cycle at 1C, and it was found that the cycle stability of the electrode with one binder (PTFE) was extremely poor. After 150 cycles, the capacity retention rate was 37%, while the capacity retention rate of the electrode with three binders (PTFECMC SBR) was 79%.

[0059] The EIS images of the electrodes obtained in Example 1, Example 2 and Example 3 are as follows: Figure 3 As shown, Figure 3 It shows that compared with the electrode with one binder (PTFE), the electrode with three binders (PTFE CMC SBR) has a much lower impedance in the high and medium frequency region, corresponding to the charge transfer resistance Rct. This indicates that the electrode with three binders (PTFE CMC SBR) can promote the transmission of lithium ions and the conduction of electrons in the battery.

[0060] The combination of sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) is often used as a binder for aqueous slurries. The carboxyl groups (-COOH) on CMC interact with the Li+ on the surface of the active material to accelerate the transmission of lithium ions. Adding SBR can enhance the flexibility of the dry electrode, making it less prone to breakage and conducive to the conduction of electrons.

[0061] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a lithium manganese iron phosphate high energy density dry electrode, characterized in that: include: Weighing lithium manganese iron phosphate, conductive carbon black, carbon nanotubes and a binder according to a first mass ratio; Putting weighed carbon nanotubes in a container, adding anhydrous ethanol and performing ultrasonic treatment to obtain a first solution; pouring weighed lithium iron manganese phosphate and conductive carbon black into the first solution, performing ultrasonic treatment again to obtain a second solution, and drying the second solution to obtain a powder; The powder is mixed with a weighed binder and ball-milled to obtain a flocculent material, and the flocculent material is roll-pressed to obtain an electrode.

2. The method for preparing a lithium manganese iron phosphate high energy density dry electrode according to claim 1, characterized in that: The first mass ratio is 85:5:5:

5.

3. The method for preparing a lithium manganese iron phosphate high energy density dry electrode according to claim 1, characterized in that: The mass ratio of anhydrous ethanol to carbon nanotubes is 500:1-750:

1.

4. The method for preparing a lithium manganese iron phosphate high energy density dry electrode according to claim 1, characterized in that: The ultrasonic treatment was as follows: the ultrasonic power was set to 300 W, and the ultrasonic treatment was performed for 2 seconds and then 1 second, for a total of 30 minutes.

5. The method for preparing a lithium manganese iron phosphate high energy density dry electrode according to claim 1, characterized in that: The second solution is dried in an oil bath to obtain powder, wherein the temperature of the oil bath drying is 60° C. and the drying time is 15 h.

6. The method for preparing a lithium manganese iron phosphate high energy density dry electrode according to claim 1, characterized in that: The binder includes at least one of polytetrafluoroethylene (PTFE), carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR).

7. The method for preparing a lithium manganese iron phosphate high energy density dry electrode according to claim 6, characterized in that: The binder is PTFE; or the binder is a mixture of PTFE and CMC, with the mass ratio of PTFE to CMC being 3:2; or the binder is a mixture of PTFE, CMC and SBR, with the mass ratio of PTFE, CMC and SBR being 2.5-3.5:0.7-1.3:

1.

8. The method for preparing a lithium manganese iron phosphate high energy density dry electrode according to claim 1, characterized in that: The powder and the weighed binder are weighed according to a second mass ratio, and after weighing, they are put into a ball mill for ball milling, wherein the rotation speed is 300 rpm and the ball milling time is 8 hours.

9. The method for preparing a lithium manganese iron phosphate high energy density dry electrode according to claim 1, characterized in that: The flocculent material is placed on a roller press and rolled for multiple times to reduce the thickness. When the thickness reaches 165-175 μm, the rolling is stopped to obtain an electrode.

10. A binder for lithium manganese iron phosphate high energy density dry electrode, characterized in that: The binder is a mixture of PTFE, CMC and SBR, and the mass ratio of PTFE, CMC and SBR is 2.5-3.5:0.7-1.3:1.